Non-Perturbative Qft Methods and Their Applications : Proceedings of the Johns Hopkins Workshop on Current Problems in Particle Theory 24, Budapest, Hungary 19-21 August 2000. - Palla, L. (World Scientific Publishing Company, 2001)
Contents: Conformal Boundary Conditions - and What They Teach Us (V B Petkova & J-B Zuber) A Physical Basis for the Entropy of the AdS3 Black Hole (S Fernando & F Mansouri) Spinon Formulation of the Kondo Problem (A Klümper & J R Reyes-Martinez) Boundary Integrable Quantum Field Theories (P Dorey) Finite Size Effects in Integrable Quantum Field Theories (F Ravanini) Nonperturbative Analysis of the Two-Frequency Sine-Gordon Model (Z Bajnok et al.) Screening in Hot SU(2) Gauge Theory and.